Robot polishing control with an active end effector based on macro-micro mechanism and the extended Preston's law. Issue 1 (2022) - Kakinuma, Yasuhiro; Ogawa, Shotaro; Koto, Katsuki
Abstract: There is a strong demand for automating the rough polishing process in plastic-mold manufacturing. In this study, with the active end effector being capable of fast force control and dynamic spindle control, a robot polishing control system based on a macro-micro-mechanism was built, which controls all parameters related to Preston's law and can be linked with computer-aided manufacturing. Based on the extended Preston equation, a polishing control algorithm that achieves uniform surface quality and uniform removal depth was proposed. The spherical rough polishing test on carbon steel demonstrated the efficacy of the proposed robot polishing control.